Quantitative computed tomographic assessment of fresh autogenous bone grafts to the maxilla - NOSAKA, Yasuhiro; HONDA, Masaki; TAKEUCHI, Manabu; SAWAI, Toshihiro; WATANABE, Kazuyo; NAKAI, Hideki; OZEKI, Kenji; FUJIMOTO, Takehiro; NIIMI, Atsushi; GOTO, Yasuyuki; UEDA, Minoru (Japanese Journal of Oral and Maxillofacial Surgery, 1996)
Dual-energy quantitative computed tomography (DEQCT) is useful in the quantitative analysis of bone mineral content (BMC). This study describes the use of DEQCT in the quantitative evaluation of the BMC of particulate cancellous bone and marrow grafted to the basal maxillary sinus and alveolar cleft defects. Several regions of interest (ROI) were used for analysis. In all ROI, BMC increased after the graft in all patients. An irregular ROI may be best suited for the evaluation of whole grafted bone. If the placement of root form implants is planned, evaluation of a circular ROI is useful. On the other hand, a CT-profile permitted the localization of BMC.